Informational Videos About Alcohol Use: Feasibility and Acceptability. (March 2018) - Brager, Jenna; Rodney, Tamar; Finnell, Deborah
Background: An estimated 15.1 million adults ages 18 years and older are classified with an alcohol use disorder, which includes 9.8 million men and 5.3 million women. A brief intervention is indicated for those identified to be at risk because of alcohol use.Objective: To determine the feasibility and acceptability of informational videos about alcohol use.Design: This feasibility study provided participants with the opportunity to choose one of two videos, Alcohol and the Brain or Rethinking Drinking . An online survey was administered to all study participants to identify alcohol-related risk, readiness to decrease use, and knowledge pertaining to alcohol use.Results: The two videos provided in this study were feasibly delivered in an on-line format to 129 adults, including 115 males and 5 females identified to be at risk. Knowledge scores increased only slightly. There were mixed results for the readiness scores.Conclusions: Future research should examine the efficacy of these two alcohol brief interventions on alcohol-related outcomes.